Rahmad Ardhani Utilization of Augmented Reality Technology as a Kidney Organ Learning Media for Hospital Administration Study Program, 'Aisyiyah University Surakarta - Rahmad Ardhani Ardhani; Muhlizardy Muhlizardy (Universitas Aisyiyah Surakarta, 2023)
AR (augmented reality), is a technology that combines two-dimensional and or three-dimensional virtual objects into a real environment and then projects these virtual objects in reality in real time. Augmented reality applies to all senses, including hearing, touch, and smell. Apart from being used in fields such as health, the military, the manufacturing industry and the world of education. This AR technology can insert certain information into the virtual world and display it in the real world with the help of equipment such as webcams, computers, Android cellphones, or special glasses. Learning media is a modern technology that can be used between educators and students in teaching and learning activities. which can connect, convey information and channel messages so as to create effective and efficient teaching and learning activities. Learning media can make communication between educators and students in the learning process. Learning media causes communication between educators and students in the learning process. Technology is currently developing very fast, including in the field of education such as augmented reality. AR learning media can visualize abstract concepts for understanding and the structure of an object model enabling AR as a more effective medium according to the objectives of the learning media. This study aims to: (1) design and build Augmented Reality learning media on the lungs; (2) knowing the performance and feasibility of Augmented Reality as a learning medium. Keywords: augmented reality, Learning Media, Learning Media